The 2022 February 15 Solar Energetic Particle Event at Mars: A Synergistic Study Combining Multiple Radiation Detectors on the Surface and in Orbit of Mars With Models - Zhang, J. (John Wiley and Sons Inc, 2025)
On 2022-02-15, solar eruptions caused one of the most intensive Solar Particle Events (SPEs) in Solar Cycle 25 observed at various heliospheric locations. This study focuses on the enhancements of energetic proton flux observed by multiple detectors located at the orbit and on the surface of Mars. We carry out the first analysis by the Mars Energetic Particle Analyzer (MEPA) instrument on board the Chinese Tianwen-1 spacecraft (TW-1) at Mars orbit which also serves to validate the instrument's capability to measure protons of up to 100 MeV. We reconstruct the event spectrum up to 1 GeV and further model the event doses at Mars's orbit and surface which are then validated against the corresponding dosimetry data. Our study utilizes all available radiation detectors at Mars, advances our understanding of Mars's radiation environment induced by large SPEs, and emphasizes the necessity of continuous and synergistic radiation monitoring at Mars.